Short term effects of clear cutting on the regeneration of sub-arctic birch forest following severe outbreaks by geometrid moths - Klinghardt, Moritz (UiT Norges arktiske universitet, 2013)
Birch forests in northern Fennoscandia experience re-occurring mass outbreaks of pest insects often resulting in severe defoliation. Here I test whether systematic clear cutting can accelerate the forest regeneration after outbreaks with uncut control plots as comparison. Basal shoot abundance was used as a main indicator for recovery but comprehensive data sampling also included the abundance of birch saplings, herbivore presence and understorey vegetation. Treatment responses of basal shoots were analyzed with generalized linear mixed models. Effects were distinguished between oligotrophic (poor) and eutrophic (rich) forest types, which were validated using vegetation data in a multi response permutation procedure. Results showed a highly significant increase of basal shoots throughout clear cut plots, with varying rich-poor differences between the two field sites. Forest regeneration through saplings showed only little improvement within the first years of the experiment.